(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The Judiciary has evolved over time, becoming a powerful instrument for defending fundamental rights. It is undeniable that the judiciary has played an important role in evaluating, applying and transforming established law in the light of constitutional principles and norms, legitimizing the rights won over time as a result of the evolution of peoples, and valuing the realization of social rights with a high degree of creativity. With a view to closely observing this evolution, this article will attempt to highlight the work of the Magistrate in the application of the Law, whose powers are conferred on him by the Federal Constitution, making use of his creative independence, whose actions, in some cases, create rights, often based on a sense of "natural justice". For many, the power of the judge does not go beyond what the law authorizes and, in this sense, does not achieve justice. For those who think this way, law is an exact science, which is not true. Interpretation, in this context, plays a fundamental role, as it moves with the evolution of the times, and this is the mainspring for saying the law, because the interests defended by the Judge must be committed to the fundamental rights of citizens, as the action of the Jurisdictional Power synthesizes the emanation of one of the Powers of the Democratic State, alongside the Executive and Legislative Powers. We can’t talk about applying the law without knowing what it means, where it comes from, who it is aimed at and how it should be used, so a brief look at the procedural aspects surrounding the issue is necessary.